Analisis Postur Kerja Pekerja Menggunakan Metode Quick Exposure Check di PT XYZ - Syafa Fadhilla Krishna Purba; Wahyudin Wahyudin (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2022)
PT XYZ is a Machining-Engineering and Fabrication service provider company located in the Jababeka Cikarang Industrial Area. PT XYZ has 5 production workstations, namely a CNC lathe machine workstations, Two CNC milling stations, namely CNC milling 1 and CNC milling machines 2, and two manual machine stations, namely Centerless Grinding 1, and Centerless Grinding 2. When carrying out production activities, workers must pay attention to safety and work posture because non-ergonomic body movements can cause injury. Therefore, this study aims to detect PT. XYZ’ workstations that are not ergonomic and identify work postures of workers' bodies parts that are risk of Musculoskeletal Disorders complaints by the Quick Exposure Check method. This method was chosen because the assessment is carried out based on two points of view, namely observers and workers to minimize bias in subjective judgments. Based on the results of research on 5 workers, the research results obtained 3 workstations that are not ergonomic. This is because the action level at the workstation is at a range of 71-100% which is included in level 4 so corrective action is needed right now. 2 workstations have a high risk of experiencing Musculoskeletal Disorders in the back, wrists, and neck. Whereas 1 workstation has a very high and high risk of experiencing complaints of Musculoskeletal Disorders in the neck and wrists. Thus, it is necessary to propose actions to improve work posture so that workers can work ergonomically. Keywords: Musculoskeletal Disorders, Quick Exposure Check, Work Posture